PEMASARAN ONLINE TERHADAP PENINGKATAN PENJUALAN USAHA RUJAK CIRENG DAN CIMOL QUEEN'S - Hana Agustina Dewi; Dini Siti Nurhikmah; Yuli Kurniawati (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
The growth of the culinary business in Indonesia is currently growing rapidly, this growth is marked by the many new innovations from each region of each of these culinary products. High competition in the end raises a problem that is often faced by companies, namely the company has not been able to provide the maximum satisfaction that is really expected by consumers. There are many ways that can be achieved by companies to increase customer satisfaction, for example by paying attention to the factors of Product Quality and Service Quality provided by the company. One of the culinary fields that are currently loved by the Indonesian people are cireng and cimol. This study aims to determine consumer responses to the 4P marketing mix (product, price, location, promotion) at CIRENG AND CIMOL QUEEN'S, Surabaya. Where it is hoped that through this research can further improve the marketing mix of Cireng and Cimol to its customers. 4P Marketing Strategy (Product, Price, Place, Promotion): The results of the research through analysis describe descriptively that consumers have a variety of product factors including taste variants, content variants and packaging variants. Then Price is based on portion, price and quantity. While the action is in progress Discounts, freebies, coupons, extra portions and freebies. during place based on concept and time of sale